Keragaan Galur-Galur Harapan Padi di Lahan Rawa Lebak Dangkal Kabupaten Sorong Papua Barat Daya - Ajang Maruapey; D.W Utami; Noladi Wicaksana; Agung Karuniawan (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
Rice is one of the important food commodities in Indonesia. The extensification of swamp land is expected to play a role in supporting the increase in national rice production. The objective of this study was to evaluate the performance of promising strains of swamp rice produced by BB-Biogen breeding tolerant to Fe poisoning in the shallow swamp area of Sorong-Southwest Papua. The experiment used a randomized block design (RBD) with three replications and 17 genotypes as treatments. The observed characters include the growth and yield component characters. Data analysis included analysis of variance to find out the differences between each test lines and continued with the LSI test to obtain the expected lines that performed well and were superior in the Sorong lebak swamps. The results of the analysis of variance showed that there were significant differences in all the characters tested. The results showed that TT, JAT and JAP showed the best results including the G21 and G11 lines, the G7 line had the highest percentage of filled grain, the G6 line had the heaviest 1000 grain weight. While the G1 and G7 lines had the highest yields per plot equivalent to 6.15 and 5.92 t/ha,